Development and quality evaluation of gluten free pasta - AJNA ALAVUDEEN AKSHARA PRAKASH RAHUL K REMYASREE P. T; Dr. Prince M. V (Guide); Er. Sruthi P. S (Co-guide) (Tavanur 2015 Department of Food and Agricultural Process Engineering)
the major objectives of the study were to standardizing the mix composition of the GFP produced from rice, jackfruit seed flour, arrowroot flour and amarnath flour each one of which has a definite qualitative parameters such as nutritional fortification, textural qualities etc. In short the weakness of the one ingredient is the strength of the other. The second objective is to study the physical, functional, proximate and microbial characterization of the products.
Development and quality evaluation of gluten free pasta